Marine Animal Forests: Bridging Science, Policy, and Local Knowledge - ROSSI, SERGIO; BRAMANTI, LORENZO; COSTANTINI , FEDERICA; DAILIANIS , THANOS; SCHUBERT , NADINE; GEROVASILEIOU, VASILIS (Mediterranean Marine Science, 2025)
Editorial Marine Animal Forests: Bridging Science, Policy, and Local Knowledge